The Effect of Resource Consumption Accounting on Accounting Pricing Decisions- An Exploratory Study in the Men's Clothing Factory in Najaf - Malik, Yasir Sahib; Ali, Ahmed Maher Mohammed; Ojah, Hassnain Kadhim (Journal of Economic, Administrative and Legal Sciences, 2019)
The research aims to indicate role of Resource Consumption Accounting as a management and costing technique. That is compatible with the rapid developments and changes in the external environment, provided by the information and scientific basis in the allocation of indirect costs; Identifying and measuring idle power and costs contribute to scientific support accounting pricing decisions. This is in the light of the intense competition and the multiplicity of alternatives. To achieve this goal Authors selected a random sample represented in the men's clothing factory in Najaf. Sample include selected deliberate ones represented by administrative and accounting staff included (52) an individual. For test the hypothesis of the research, Authors used statistical program (SPSS), and a set of other statistical metrics. The most important conclusion is that the Resource Consumption Accounting contributes to support pricing decisions by contributing to the provision of accurate cost information, achieve cost reduction, contributes to the process of planning, improving productivity, and profitability. The most important recommendations were the need to apply the research sample to the technique of Resource Consumption Accounting, including the reduction in costs, identify and measure unused energy, and manage this energy. Which contributes to supporting accounting pricing decisions.
Keywords: resource consumption accounting; pricing decisions; accounting pricing decisions